Prediction of Ischemic Events after Percutaneous Coronary Intervention: Thrombelastography Profiles and Factor XIIIa Activity - Kreutz, Rolf P.; Schmeisser, Glen; Schaffter, Andrea; Kanuri, Sri; Owens, Janelle; Maatman, Benjamin; Sinha, Anjan; von der Lohe, Elisabeth; Breall, Jeffrey A. (TH Open, 2018)
Background High plasma fibrin clot strength (MA) measured by thrombelastography (TEG) is associated with increased risk of cardiac events after percutaneous coronary interventions (PCIs). Factor XIIIa (FXIIIa) cross-links soluble fibrin, shortens clot formation time (TEG-K), and increases final clot strength (MA).Methods We analyzed platelet-poor plasma from patients with previous PCI. Kaolin-activated TEG (R, K, MA) in citrate platelet-poor plasma and FXIIIa were measured (n = 257). Combined primary endpoint was defined as recurrent myocardial infarction (MI) or cardiovascular death (CVD). Relationship of FXIIIa and TEG measurements on cardiac risk was explored.Results FXIIIa correlated with TEG-MA (p = 0.002) and inversely with TEG-K (p < 0.001). High MA (≥35.35 mm; p = 0.001), low K (<1.15 min; p = 0.038), and elevated FXIIIa (≥83.51%; p = 0.011) were associated with increased risk of CVD or MI. Inclusion of FXIIIa activity and low TEG-K in risk scores did not improve risk prediction as compared with high TEG-MA alone.Conclusion FXIIIa is associated with higher plasma TEG-MA and low TEG-K. High FXIIIa activity is associated with a modest increase in cardiovascular risk after PCI, but is less sensitive and specific than TEG-MA. Addition of FXIIIa does not provide additional risk stratification beyond risk associated with high fibrin clot strength phenotype measured by TEG.
Keywords: thrombelastography; fibrin; factor XIII; percutaneous coronary intervention; myocardial infarction